Persepsi Konsumen dan Peluang Usaha Terhadap Obat dan Suplemen Herbal Berbahan Baku Sumberdaya Perairan di Kota Kendari - Indriyani; Riani, Irdam; Annaastasia, Nurhuda; Patiung, Seventry Meliana; Iba, Wa (Jurnal Sosial Ekonomi Perikanan, 2025)
This study aims to determine consumer perceptions and business opportunities for medicines and herbal supplements made from aquatic resources in Kendari City. There were 54 respondents in this study consisting of 4 shop owners and 50 consumers who were determined using a purposive sampling method. Data obtained from primary data, namely observation, questionnaires and interviews. Data analysis used quantitative descriptive analysis using chi square analysis method and quantitative descriptive method. The results showed that the statistical test results of the person chi square value were the relationship between age and consumer perception of 0.563, the relationship of education to consumer perception of 0.634, the relationship of income to consumer perception of 0.563. Qualitative analysis of opportunities, namely per unit which is quite attractive, affordable price, no side effects, especially the Gold-G brand which is made from sea cucumbers. Conclusions that can be drawn from the results of this study are 1). Consumer income, age, and education have no significant effect on consumer perceptions of products, prices, and product benefits. 2). The business of herbal medicines and supplements made from aquatic resources has a chance to develop in Kendari City